ANALYSIS OF DIRECT AND INDIRECT EFFECTS OF FISCAL DECENTRALIZATION ON REGIONAL DISPARITY (CASE STUDY OF PROVINCES IN EASTERN AND WESTERN OF INDONESIA, 2006-2015) - Fadli, Faishal (Journal of Indonesian Applied Economics, 2016)
This study aimed to examine the direct and indirect effects of fiscal decentralization on regional disparity through economic growth in eastern and western Indonesia. The method used in this study is Path Analysis. The variables used in this study include the General Allocation Fund (DAU/Dana Alokasi Umum), Special Allocation Fund (DAK/Dana Alokasi Khusus), Revenue Sharing Fund (DBH/Dana Bagi Hasil), local revenue (PAD/Pendapatan Asli Daerah), Economic Growth (G), and regional disparity (IW). Comparing the analysis between eastern and western of Indonesia, the results show that there is no direct effect of fiscal decentralization on regional disparity and economic growth through direct fiscal decentralization on regional disparity in both eastern and western of Indonesia. However, using some measures of fiscal decentralization, in the case of eastern of Indonesia, DAU variable has significant effect whereas in the case of western Indonesia, DBH is the only one variable that has significant effect. This is consistent with the fact that composition of the balance funds disbursed by the central government to local governments, where the greatest composition of funds in eastern Indonesia come from the General Allocation Fund which reflects the dependence of local governments to the central government and for the western region of Indonesia, DBH is the greatest reflecting the independence of the local governments. As a result, to create fiscal decentralization working it is required a greater allocation of the fund balance.